Tindakan Ultra Vires Pada Perseroan Perorangan yang Menyebabkan Penghapusan Tanggung Jawab Terbatas: Studi Komparatif Dengan Single Member Company (Sdn. Bhd) di Malaysia - Hasna Azizah (Media Hukum Indonesia (MHI), 2026)
This study examines the position and limits of liability of a sole shareholder in a Single-Member Company, including the application of the doctrines of ultra vires and piercing the corporate veil to directors’ actions that exceed their authority. Using a normative juridical approach and a comparative analysis with Malaysia’s Companies Act 2016, the research finds that Indonesian regulations remain insufficient in providing internal oversight mechanisms for companies owned by a single individual. Although the principles of asset separation and limited liability are recognized, the concentration of control in one person increases the risk of ultra vires actions, which may justify the removal of limited liability protections. Accordingly, Indonesia must strengthen its regulatory framework to ensure legal certainty and adequate protection for creditors, owners, and other stakeholders.